A critique and solution of justice, certainty, and usefulness in law enforcement in Indonesia - Muhamad Romdoni; Mawarni Fatma; Rizki Nurdiansyah; Suyanto Suyanto; Arief Fahmi Lubis (Institute Of computer Science (IOCS), 2023)
In Indonesia, law enforcement agencies do not collaborate to achieve justice. Due to the legal institution's position and status, the Supreme Court is responsible for adjudicating and deciding cases, while the executive is responsible for investigating and adjudicating. Consequently, instead of striving to uphold the law in the public interest, they typically prioritize the interests of their respective institutions. Therefore, the purpose of this study is to determine if law enforcement and judicial justice can bring harmony to those seeking justice. This study aims to provide answers through the use of juridico-philosophical methods and literature studies by conducting theoretical studies of theories of justice and their relationship to the implementation of law enforcement within the judiciary. The findings indicate that power and other powers continue to influence the judicial system as an institution whose independence in upholding law and justice is guaranteed, particularly the influence of executive power and political power. In addition, the court's function as a law enforcement agency is not entirely autonomous, so the court's primary responsibility is to promote peace and justice in society. Therefore, in order to promote a sense of tranquility among justice advocates, it is necessary to strengthen the justice system, which is their final sanctuary.